Synergy effects of copper ion in doxorubicin-based chelate prodrug for cancer chemo-chemodynamic combination therapy - Wen Zhang; Peng Zhang; Xiaopeng Xu; Minghui Li; Shasha Wang; Hongjie Mu; Kaoxiang Sun (Taylor & Francis Group, 2023)
AbstractDoxorubicin (DOX) is a commonly studied chemotherapeutic agent for the treatment of solid tumors, but the severe side effects limit its clinical application. It is shown that DOX-metal chelate has lower in vitro cytotoxicity compared with DOX, as the anthracyclines of DOX can form coordinative interaction with transition metal ions. In addition, the transition metal ions could catalyze the production of hydroxyl radicals (·OH) via Fenton/Fenton-like reactions to achieve antitumor chemodynamic therapy (CDT). In this study, copper ions (Cu2+) were applied to obtain DOX/Cu(II) prodrug, and a liposomal formulation was used to avoid the rapid blood clearance and optimize the biodistribution of this prodrug. In vitro and in vivo antitumor results demonstrated that this pH sensitive Cu-chelating prodrug can reduce adverse effects of DOX but improve the antitumor efficiency due to the combination of chemotherapy and chemodynamic therapy. Our study provided a facile and effective approach of metal-chelating prodrug strategy for combination cancer therapy strategy.